Defining the gastroesophageal junction in trauma: Epidemiology and management of a challenging injury. Issue 5 (November 2017) - Schellenberg, Morgan; Inaba, Kenji; Bardes, James M.; O'Brien, Daniel; Lam, Lydia; Benjamin, Elizabeth; Grabo, Daniel; Demetriades, Demetrios
Abstract : BACKGROUND: Injuries to the gastroesophageal (GE) junction are infrequently encountered because of the high mortality of associated injuries. Consequently, there is a paucity of literature on the patient demographics and treatment options. The aim of this study was to examine the epidemiology, surgical management, and outcomes of these rare injuries. METHODS: Patients presenting to LAC + USC Medical Center (January 2008 to August 2016) with traumatic esophageal or gastric injury (DRG International Classification of Diseases—9th Rev.—Clinical Modification and 10th Rev. codes) were extracted from the trauma registry. Patient charts were reviewed, and all patients who sustained an injury to the GE junction were enrolled. Patient demographics, injury characteristics, procedures, and outcomes were analyzed. RESULTS: Of the 238 patients who sustained an injury to the esophagus or stomach during the study period, 28 (12%) were found to have a GE junction injury. Mean age was 26 years (range, 14–57 years), 89% male. Mechanism of injury was penetrating in 96% (n = 27), the majority of which were gunshot wounds (n = 22, 81%). Most patients (n = 18, 64%) were taken directly to the operating room. Ten (36%) underwent computed tomography scan before going to the operating room, all demonstrating a GE junction injury. All patients underwent repair via laparotomy. One (4%) also required thoracotomy to facilitate delayed reconstruction. GE junction injuries were typically managed with primary repair (n = 22, 79%). Associated injuries were frequent (n = 26, 93%), and injury severity was high (mean Injury Severity Score, 25 [9–75]). Mortality was 25% (n = 7), and all patients required intensive care unit admission. Most did not require total parenteral nutrition (n = 25, 89%) or a surgically placed feeding tube (n = 26, 93%). Of the 13 patients who presented for clinical follow-up, all but one (n = 12, 92%) were eating independently by the first clinic visit. CONCLUSION: GE junction injuries are uncommon and occur almost exclusively after penetrating trauma. Patients are severely injured with a high mortality rate and frequently have associated intracavitary injuries. Most can be fixed through the abdomen alone and do not require thoracotomy for repair. Despite the severity of injuries, the majority of survivors are eating independently by the first clinic visit. LEVEL OF EVIDENCE: Epidemiological, level V.